Epidemiological approach to emergent cranial surgery of cranial traumas (Italian Journal of Public Health, 2008)
Objective: In this study, we aim to define the emergent cranial surgery of cranial trauma cases in terms of the reason of occurance, diagnosis, prognostic factors and results. Methods: 153 cases hospitalized in our clinic during a four year period were statistically analysed in accordance with trauma etiology, age, gender, application GCS (Glascow Coma Score) mortality rate, location and established patology.Results: 76% (116) of the 153 cases were male. The most frequent etiological reasons were, in descending order, traffic accident 52% (n = 80), fall 34% (n = 53), direct trauma to the head 14(n =20). 45% (n = 69) were diagnosed epidural haematomas, 26% (n = 40) were diagnosed depression fractures and 3% (n = 5) were diagnosed intracerebral haematomas. A meaningful statistical difference was found in the comparison of the diagnosis regarding gender (p=0,012) age group (p=0,0282) and GCS (p=0,0001).Conclusions: In order to prevent cranial traumas, studies aimed at minimizing traffic accidents should be undertaken. The most essential action after the accident has occured is triage, and this is of great importance in order to establish communication among the health institutions.
Keywords: Cranial trauma; Glascow Coma Score; trauma etiology